Biliary candidiasis mimicking IgG4‐related disease in a patient with normal immunity. Issue 3 (4th May 2022) - Bian, Wenjie; Zhong, Yuchao; Zhang, Xia; Chen, Hongbin; Feng, Ruie; Zhang, Xinyu; Shen, Danhua; Liu, Yanying
Abstract: Purpose: To report a rare case of biliary candidiasis in a host with normal immunity. Methods: Laboratory tests indicated an elevated G level of 1000 pg/ml. Microscopic examination of pathological sections demonstrated multiple, narrow base, budding yeast cells following Grocott's methenamine silver staining and periodic acid‐Schiff staining. Subsequent sequence analysis supported the diagnosis of biliary candidiasis. Results: A 31‐year‐old previously healthy man developed obstructive jaundice under no obvious inducement. He experienced cholecystectomy and biliary drainage. Surgical specimens revealed granulomatous chronic inflammation in the gallbladder, liver, bile ducts and mesenteric lymph nodes. He was misdiagnosed with tuberculosis and received antituberculosis treatment. However, his condition did not improve. He was finally diagnosed with biliary candidiasis and administered the antifungal treatment with fluconazole. His symptoms improved after such treatment. Conclusions: We reported a case of biliary candidiasis that mimicked IgG4‐RD in a host with normal immunity. Our findings highlighted the need for pathological diagnosis in patients with symptoms resembling IgG4‐RD. Abstract : Imaging, pathological, and the second generation sequencing evidence of Candida albicans . (A) Abdominal magnetic resonance imaging before and after treatment. Upper left: Markedly thickened biliary duct wall and luminal stenosis. Lower left: A swollen pancreas, especially in the head region, with a dilated pancreatic duct. Upper right: Alleviation of the disease by bile duct stenosis. Lower right: Alleviated pancreatic swelling. (B) Periodic acid‐Schiff staining demonstrated multiple, narrow base, budding yeast cells. (C) The sequencing data indicative of Candida albicans . The abscissa represents the position in the C. albicans genome and the ordinate represents the sequence depth. Key points: Biliary candidiasis could mimic IgG4‐RD in a patient with normal immunity. IgG4‐RD should be diagnosed carefully especially in some rare cases.